Strategi Pembelajaran Pendidikan Agama Kristen di Era Society 5.0 - Ya’aman Gulo; Talizaro Tafonao; Rita Evimalinda (Sekolah Tinggi Teologi Yerusalem Baru, Manado, 2021)
Abstract: The purpose of writing this article is to explain learning strategies that are relevant in the 5.0 era of society in learning Christian religious education. The author observes that the learning strategy is a means to achieve the learning objectives that have been set. Because one of the challenges faced by teachers today is the development of technology. The era of society 5.0 demands a teacher to be more creative, innovative and informative. That's why, the author reviews this paper to provide some tricks and tips so that teachers are able to compete and use appropriate learning strategies in the era of society 5.0. The method used in this study is a descriptive qualitative research method by examining the learning strategies of Christian religious education in the era of society 5.0. The method used in this study is a descriptive qualitative research method by examining the learning strategies of Christian religious education in the era of society 5.0. The results obtained in this study show that one of the learning strategies for Christian religious education in the era of society 5.0 that are still relevant are participatory strategies, inquiry strategies, discovery learning strategies, cooperative strategies, and blended learning strategies. Thus, the era of society 5.0 is a community concept that was developed to apply and balance the use of technology in everyday life so that access occurs in virtual space and physical space to solve social problems in order to create super smart humans.Abstrak: Tujuan penulisan artikel ini adalah menjelaskan strategi pembelajaran yang relevan di era society 5.0 dalam pembelajaran Pendidikan Agama Kristen. Penulis mengamati bahwa strategi pembelajaran merupakan sarana untuk mencapai tujuan pembelajaran yang sudah ditetapkan. Karena salah satu tantangan yang dihadapi oleh guru saat ini adalah perkembangan teknologi. Era society 5.0 menuntut seorang guru untuk lebih kreatif, inovatif dan informatif. Oleh karena itu, penulis mengkaji tulisan ini untuk memberi beberapa trik dan tips agar guru-guru mampu bersaing dan menggunakan strategi pembelajaran yang tepat di era society 5.0. Metode yang digunakan dalam penelitian ini adalah metode penelitian kualitatif deskriptif dengan mengkaji strategi pembelajaran Pendidikan Agama Kristen di era society 5.0. Hasil yang dapatkan dalam kajian ini menunjukan bahwa salah satu strategi pembelajaran Pendidikan Agama Kristen di era society 5.0 yang masih relevan adalah strategi partisipatif, strategi inkuiri, strategi discovery learning, strategi koorperatif, dan strategi blended learning. Dengan demikian bahwa era society 5.0 adalah sebuah konsep masyarakat yang dikembangkan untuk mengaplikasikan dan menyeimbangkan penggunaan teknologi dalam kehidupan sehari-hari sehingga terjadinya akses dalam ruang virtual dan ruang fisik untuk memecahkan masalah sosial agar terciptanya manusia yang super smart.